Design and development of sensorless based 5-DOF bilaterally controlled surgical manipulator: A prototype - Sakol Nakdhamabhorn; M. Branesh Pillai; Jackrit Suthakorn (Institute of Advanced Engineering and Science, 2021)
Minimally invasive surgery (MIS) is one of the most challenging tasks in surgical procedures due to the lack of visibility of the surgical area, instrument orientation, and depth perception. A tele-operated robot assisted minimally invasive surgery is developed to enhance a surgeon's hand dexterity and accuracy. To perform MIS, the surgeon controls a slave manipulator via a master manipulator, so the force feedback and motion feedback are required to imitate an amount of action and reaction force between master and slave manipulator. The complicated MIS requires more complex surgical manipulator with multi DOFs and multiple force feedback. The limitation of multiple DOFs force feedback is a bandwidth of torque sensors. Therefore, this study proposes a sensorless based 5-DOF Bilaterally controlled surgical manipulation. In this research disturbance observer (DOB) is used to identify the internal disturbance of the system, which is used to estimate the reaction torque. This research mainly focuses on a 5-DOF bilaterally controlled surgical manipulator to maintain a position and additional force. The result of torque error in contact motion is less than 2%, the non-contact motion error is not over 5%, and it is evident that the error is always less than 0.3% for the position response.